2007
DOI: 10.1111/j.1600-0838.2006.00619.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between quadriceps femoris muscle volume and muscle torque after anterior cruciate ligament repair

Abstract: This study was performed to obtain evidence regarding bilateral hindrance of motor unit (MU) recruitment in the quadriceps femoris (QF) of patients with anterior cruciate ligament (ACL) reconstruction. The subjects included 70 patients who underwent ACL reconstruction and 35 healthy subjects. To identify the muscle torque per unit volume (MTPUV), the peak torque of each velocity of isokinetic performance was divided by muscle volume of the QF measured by a series of cross-sectional images obtained by magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
55
2
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 24 publications
10
55
2
2
Order By: Relevance
“…With the greatest ES and narrowest 95% CI (Table 3), this clinically meaningful and statistically different decrease in peak torque indicated a deficit in quadriceps function that, in part, may be explained by a mechanical change in muscle due to a loss of sarcomeres in parallel or a change in the pennation of the muscle. 27,32,33,35À37 Whereas we did not directly analyze these possibilities, several authors using imaging technologies found that patients with ACLR experienced reduced total muscle volume 38,39 and anatomic CSA. 40 Recently, Kuenze et al 41 used magnetic resonance imaging and custom-written software to quantify individual variations in quadriceps muscle volume and reported that reductions in the vastus intermedius muscle belly were most strongly related to a decline in isometric quadriceps force production.…”
Section: Isometric Interlimb Asymmetriesmentioning
confidence: 99%
“…With the greatest ES and narrowest 95% CI (Table 3), this clinically meaningful and statistically different decrease in peak torque indicated a deficit in quadriceps function that, in part, may be explained by a mechanical change in muscle due to a loss of sarcomeres in parallel or a change in the pennation of the muscle. 27,32,33,35À37 Whereas we did not directly analyze these possibilities, several authors using imaging technologies found that patients with ACLR experienced reduced total muscle volume 38,39 and anatomic CSA. 40 Recently, Kuenze et al 41 used magnetic resonance imaging and custom-written software to quantify individual variations in quadriceps muscle volume and reported that reductions in the vastus intermedius muscle belly were most strongly related to a decline in isometric quadriceps force production.…”
Section: Isometric Interlimb Asymmetriesmentioning
confidence: 99%
“…Strength was tested at 608/s, which is a common angular velocity for assessing strength before and after ACL reconstruction. 8,10,11,19 Three maximal voluntary concentric contractions were performed for each muscle group tested. The peak value over those 3 repetitions was normalized to participant body mass (kg) and used to quantify strength (Nm/kg).…”
mentioning
confidence: 99%
“…1 Lower extremity muscle weakness, particularly in the quadriceps and hamstrings, also is reported commonly after ACL injury and reconstruction, often lingering well beyond the postoperative rehabilitation period. 2,3 Quadriceps strength deficits in the injured limb reportedly range from 5% to 40% [2][3][4][5][6][7][8][9][10] and have been noted as long as 7 years after surgery. 3 Hamstrings strength deficits in the injured limb have been reported to range from 9% to 27% 2,3,5,8,9,11 and have been reported 3 years after surgery.…”
mentioning
confidence: 99%
“…Muscle atrophy and activation failure may contribute [4]. It has been mentioned that ACL reconstruction and injured limb decreased from 5% to 40% in strength of the quadriceps muscle [5,6,7]. It can be concluded that other factors (physical fitness) such as maximal power is affected by ACL reconstruction.…”
mentioning
confidence: 99%